Endotoxin Engages Mitochondrial Quality Control via an iNOS-Reactive Oxygen Species Signaling Pathway in Hepatocytes. (24th October 2019) - Cyr, Anthony; Chambers, Lauran; Waltz, Paul K.; Whelan, Sean P.; Kohut, Lauryn; Carchman, Evie; Dyer, Mitchell; Luciano, Jason; Kautza, Benjamin; Gomez, Hernando D.; Otterbein, Leo E.; Rosengart, Matthew R.; et al.
Abstract : Background . Organ injury and dysfunction in sepsis accounts for significant morbidity and mortality. Adaptive cellular responses in the setting of sepsis prevent injury and allow for organ recovery. We and others have shown that part of the adaptive response includes regulation of cellular respiration and maintenance of a healthy mitochondrial population. Herein, we hypothesized that endotoxin-induced changes in hepatocyte mitochondrial respiration and homeostasis are regulated by an inducible nitric oxide synthase/nitric oxide (iNOS/NO)-mitochondrial reactive oxygen species (mtROS) signaling axis, involving activation of the NRF2 signaling pathway. Methods . Wild-type (C57Bl/6) or iNos -/- male mice were subjected to intraperitoneal lipopolysaccharide (LPS) injections to simulate endotoxemia. Individual mice were randomized to treatment with NO-releasing agent DPTA-NONOate, mtROS scavenger MitoTEMPO, or vehicle controls. Other mice were treated with scramble or Nrf2 -specific siRNA via tail vein injection. Primary murine hepatocytes were utilized for in vitro studies with or without LPS stimulation. Oxygen consumption rates were measured to establish mitochondrial respiratory parameters. Western blotting, confocal microscopy with immunocytochemistry, and rtPCR were performed for analysis of iNOS as well as markers of both autophagy and mitochondrial biogenesis. Results . LPS treatment inhibited aerobic respiration in vitro in wild-type but not iNos -/- cells. Experimental endotoxemia in vivo or in vitro induced iNOS protein and mtROS production. However, induction of mtROS was dependent on iNOS expression. Furthermore, LPS-induced hepatic autophagy/mitophagy and mitochondrial biogenesis were significantly attenuated in iNos -/- mice or cells with NO or mtROS scavenging. These responses were rescued in iNos -/- mice via delivery of NO both in vivo and in vitro. Conclusions . These data suggest that regulation of mitochondrial quality control following hepatocyte LPS exposure is dependent at least in part on a NO-mtROS signaling network. Further investigation to identify specific agents that modulate this process may facilitate the prevention of organ injury in sepsis.